2018
DOI: 10.4102/phcfm.v10i1.1998
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum: Factors related to married or cohabiting women’s decision to use modern contraceptive methods in Mafikeng, South Africa

Abstract: No abstract available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 0 publications
6
17
1
2
Order By: Relevance
“…The education status of women or husbands were the factors that affect the decisionmaking of women. 4,10,15 Similarly, those women who have less than 5 children were less likely to decide by their husbands than jointly as compared to those women who have greater than 5 children. The result indicated that women who have a lower number of children have more deciding power than those who have more than 5 children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The education status of women or husbands were the factors that affect the decisionmaking of women. 4,10,15 Similarly, those women who have less than 5 children were less likely to decide by their husbands than jointly as compared to those women who have greater than 5 children. The result indicated that women who have a lower number of children have more deciding power than those who have more than 5 children.…”
Section: Discussionmentioning
confidence: 99%
“…4 The joint decision of the current finding was relatively higher than the study done in South Africa and Bangladesh, in which about 45% and 61% of women decide on the matter of contraceptive use jointly with their husbands or partners, respectively. 6,15 The possible explanation for the difference might be due to differences in socioeconomic differences between the countries, for example, in South Africa the majority of women decide by themselves. This may be because of the South African women were more educated than our study area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, uptake of family planning can improve women's socioeconomic status and increase their level of agency. (14)(15)(16)(17)(18)(19)(20)(21)(22). In rural Tanzania, lack of communication among couples about family planning was previously identi ed as a barrier to uptake (23,24).…”
Section: Introductionmentioning
confidence: 99%